Pengaruh Media Game Wordwall terhadap Kemampuan Literasi Sains Siswa Sekolah Dasar: The Influence of Wordwall Game Media on Elementary School Students' Science Literacy Skills - Feby Inge Dwiyanti; Kiki Pratama Rajagukguk; Pradana Chairy Azhar (ITScience (Information Technology and Science), 2024)
This study aims to analyze the effect of Wordwall game media on elementary school students' scientific literacy skills. This study was conducted using an experimental method involving two groups: an experimental group using Wordwall media and a control group using conventional learning methods. Data was collected through pre-tests and post-tests designed to measure students' scientific literacy skills before and after treatment. The analysis showed that the experimental group's average pre-test score was 57.8, while the control group was 56.0. After treatment, the average post-test score of the experimental group increased to 80.2, while the control group only reached 76.6. Statistical analysis using the t-test showed a significant difference between the two groups (p <0.05), indicating that Wordwall media improved scientific literacy skills. The sample of this study consisted of elementary school students taken from two different classes, with each group consisting of 20 students. The results showed that using Wordwall game media significantly improved students' scientific literacy skills compared to conventional methods. Thus, Wordwall Press can be an alternative and innovative way to improve elementary school students' scientific literacy. This study's results indicate a significant difference between students' scientific literacy abilities before and after treatment. This study also revealed that using Wordwall improves the understanding of scientific concepts and motivates students to be more active in learning.